Rectal Metastasis from Early-Stage Endometrial Carcinoma Not Associated with Endometriosis: A Case Report and Literature Review - Krsteska, Blagica; Risteski, Vladimir; Jovcheva, Ana; Antovikj, Svetozar (Kurume University School of Medicine, 2025)
Endometrial cancer (EC) is the third most common malignancy in woman with excellent prognosis when diagnosed in early-stage. Recurrences are extremely rare in Stage I EC especially in rectum when not associated with endometriosis. We present a case of rectal metastasis from endometrial carcinoma after 8 years of primary diagnosis. A review of the literature showed only 6 published cases.
Keywords: secondary carcinoma; rectum; endometrial carcinoma; recurrence; rectal metastasis